Optimalisasi Peran Guru Pendidikan Agama Islam Sebagai Konselor dalam Mengatasi Masalah Belajar Siswa - Yuhana, Asep Nanang; Aminy, Fadlilah Aisah (Jurnal Penelitian Pendidikan Islam, 2019)
This article aims to look for learning problems faced by students of class VI MIS Handapherang-Ciamis, the teacher's efforts and the steps taken to overcome these problems. By using qualitative-descriptive method, research concludes; First, students experience difficulty in reading and writing. The problem factor comes from the parents and from the students themselves. Second, the efforts made by the class teacher at school to grade VI students who experience learning problems that is maximizing their sense of hearing by listening to the teacher when explaining the learning material, guided when the child does not understand the learning material and finally teacher guided when the child does not pay attention to the teacher explaining in learning process. Third, the teacher's stages in overcoming student learning problems starts from determining the problem to solving the problems that occur in students of class VI MIS Handapherang.